Epiproteome profiling of cadmium‐transformed human bronchial epithelial cells by quantitative histone post‐translational modification–enzyme‐linked immunosorbent assay - Liang, Zhan‐Ling; Wu, Dan‐Dan; Yao, Yue; Yu, Fei‐Yuan; Yang, Lei; Tan, Heng Wee; Hylkema, Machteld N.; Rots, Marianne G.; Xu, Yan‐Ming; Lau, Andy T. Y. (Journal of applied toxicology, 2018)
Cadmium (Cd), a carcinogenic toxic metal, is pervasively distributed in the soil, water and air. Chronic exposure to Cd has been correlated to lung disease development including cancers. Although many studies have been conducted to investigate the proteome response of cells challenged with Cd, the epiproteomic responses (i.e., global histone post‐translational modifications [PTMs]), particularly in human lung cells, are largely unexplored. Here, we provide an epiproteome profiling of human bronchial epithelial cells (BEAS‐2B) chronically treated with cadmium chloride (CdCl2), with the aim of identifying global epiproteomic signatures in response to Cd epigenotoxicity. Total histone proteins from Cd‐treated and untreated BEAS‐2B cells were isolated and subject to quantitative histone PTM–enzyme‐linked immunosorbent assay using 18 histone PTM antibodies. Our results unveiled that chronic Cd treatment led to the marked downregulation of H3K4me2 and H3K36me3 and upregulation of H3K9acS10ph, H4K5ac, H4K8ac and H4K12ac PTM marks. Cd‐treated cells exhibit transformed cell properties as evidenced by enhanced cell migration and the ability of anchorage‐independent growth on soft agar. Notably, treatment of Cd‐transformed cells with C646, a potent histone acetyltransferase inhibitor, suppressed the expression of mesenchymal marker genes and cell migration ability of these cells. Taken together, our studies provide for the first time the global epiproteomic interrogation of chronic Cd‐exposed human lung cells. The identified aberrant histone PTM alterations associated with Cd‐induced epigenotoxicity likely account for the epithelial−mesenchymal transition and neoplastic survival of these cells. Here, we provide an epiproteome profiling of human lung cells chronically treated with cadmium chloride (CdCl2), with the aim of identifying global epiproteomic signatures associated with Cd‐induced epigenotoxicity. Notably, among the 18 histone post‐translational modification marks examined, a marked decrease of the levels of histone H3K4me2 and H3K36me3 and increase of H3K9acS10ph, H4K5ac, H4K8ac and H4K12ac were found in chronic Cd‐exposed cells. These differential post‐translational modification marks might likely govern the epithelial−mesenchymal transition and neoplastic survival of these cells.